Difference in Lesion Reactivation between Pure Type 2 and Mixed Type 1 and 2 Macular Neovascularization and its Influence on Long-Term Treatment Outcomes. (19th May 2023) - Kim, Jae Hui; Kim, Jong Woo; Kim, Chul Gu
ABSTRACT: Purpose: To compare lesion reactivation and treatment outcomes between pure type 2 and mixed type 1 and 2 macular neovascularization (MNV) treated with anti-vascular endothelial growth factor (VEGF). Methods: This retrospective study included 155 patients diagnosed with type 2 MNV. After the initial loading injections, as-needed retreatment was provided. The difference in first lesion reactivation after the initial treatment was evaluated between pure type 2 MNV (pure type 2 group, n = 37) and mixed type 1 and 2 MNV (mixed group, n = 118). The degree of change in the best-corrected visual acuity (BCVA) was also compared between the two groups. Results: The mean follow-up period was 32.7 ± 13.7 months. Lesion reactivation differed significantly between the type 2 (60.0%) and mixed (84.5%) ( P = .004) groups. The degree of visual change during the follow-up period also differed significantly between the pure type 2 (mean 2.8 lines of improvement) and mixed (mean 0.2 lines of deterioration) ( P = .008) groups. In multivariate analysis, lesion type ( P = .012) and baseline visual acuity ( P = .002) were significantly associated with ≥2 lines of visual improvement Conclusions: Lesion reactivation and treatment outcomes differed between pure type 2 and mixed type 1 and 2 MNV. These results suggested the need for different treatment strategies for these two MNV subtypes.